The effect of oleic acid as post spinning treatment on tensile strength of polyacrylonitrile fibers - Salleh, S.N.M. (American Institute of Physics Inc., 2017)
Carbon fiber precursor was derived from Polyacrylonitrile (PAN) polymer, pitch based and cellulose rayon. Until now, the best precursor for carbon fibre is PAN polymer. This is because PAN polymer precursor have higher carbon content when subjected to heat treatment process. After spinning process, the PAN fibre will be soaked in a chemical before proceed to heat treatment process. The process is known as post spinning treatment process. In this study, oleic acid and the commercial chemical were applied as post treatment spinning chemical. After post spinning treatment, the fibre will be heat treated in 2 temperature zone represent stabilize and pre-carbonized region. The stabilize region is fixed at 250°C and the pre-carbonized region at 500°C. After heat treatment process, the fibre will be mechanically characterized using the low force single column universal tensile machine. Scanning Electron Microscope (SEM) micrograph was used to determine fibre diameter and surface microstructure. From the study, the tensile strength of PAN fiber post treated with oleic acid was lowered almost 50. For pre carbonized process, PAN fiber post treated with an oleic acid increase by 73. This show that oleic acid can be used as post spinning treatment chemical in carbon fibre conversion process. © 2017 Author(s).